Análise da perda dentária em adultos e idosos associada à condições sindêmicas e a autopercepção de saúde bucal em uma capital do nordeste: estudo BRAZUCA - Pereira, Isabel Ferreira (2023)
Introduction: Health surveys are essential to understand the real needs of the population, their living and health conditions. BRAZUCA is a population-based study, carried out in the city of Natal, Rio Grande do Norte, with adults and elderly people, intending to investigate possible living and health conditions related to food insecurity. A brief oral health questionnaire was included in the study and enabled a municipal epidemiological assessment of the risk of tooth loss. Objectives: To evaluate the risk of tooth loss in an adult and elderly population living in Natal/RN, in the face of syndemic conditions and self-perception of oral health. Methodology: This is an observational epidemiological study, with a cross-sectional design, carried out as part of the population-based multicenter survey BRAZUCA - Brazilian Usual Consumption Assessment. A multi-stage cluster probabilistic sampling plan was used. 27 census tracts were selected. Results: 441 people of both sexes were evaluated, the majority were female (58.2%), non-white skin color (64.7%), adult (53.8%), with 1 to 9 years of study (43 .8%) and who lived in a neighborhood with a sectoral income of less than 2 minimum wages (76.4%). Regarding the main outcomes, 85.4% of individuals lost a tooth, despite 49.1% of those interviewed declaring their health as very good to regular. Conclusion: There is a higher chance of tooth loss in individuals with associated determining conditions and who consider their health to be poor or very poor.